Design of experiment to predict the time between hydrogen purges for an air-breathing PEM fuel cell in dead-end mode in a closed environment. (14th April 2021) - Chiche, Ariel; Lindbergh, Göran; Stenius, Ivan; Lagergren, Carina
Abstract: Fuel cells are promising technologies for zero-emission energy conversion. They are used in several applications such as power plants, cars and even submarines. Hydrogen supply is crucial for such systems and using Proton Exchange Membrane Fuel Cell in dead-end mode is a solution to save hydrogen. Since water and impurities accumulate inside the stack, purging is necessary. However, the importance of operating parameters is not well known for fuel cells working in closed environments. A Design of Experiment approach, studying time between two purges and cell performance, was conducted on an air-breathing stack in a closed environment. The most influential parameters on the time between two purges are the relative humidity and the current load. Convection in the closed environment can decrease the stability of the fuel cell. A linear model with interactions between these last three parameters was found to accurately describe the studied responses. Highlights: PEM fuel cell in dead-end mode in a closed environment with voltage drop purging. Time between two needed purges and overall performance of the fuel cell monitored. Design of Experiments with 6 parameters to find the optimum operation conditions. Low current and high relative humidity increase the fuel cell performance.